Pendampingan Kolaboratif Orang Tua dan Guru Berbasis Strategi Komunikasi Efektif dalam Membentuk Karakter Religius Siswa - Supian, Supian; Sobri, Muhammad; Vahlepi, Sahrizal; K.A. Rahman, K.A. Rahman; Muspawi, Mohamad; Zulaika, Zulaika (Civiliza Publishing, 2025)
The community service program at MI Ihsaniyah, Jambi City, aimed to strengthen the development of students’ religious character through collaborative mentoring between teachers and parents, based on effective communication. The background of this initiative was the low intensity of school–family communication and the lack of alignment in character education between home and school. The Participatory Action Research (PAR) approach was employed, involving teachers, parents, lecturers, and students in the planning, implementation, and evaluation processes. The activities included monthly communication forums, training on effective communication strategies for parents, and ongoing mentoring. As a result, there was an improvement in the quality of two-way communication, alignment of the values instilled, and consistency in students’ religious behavior both at school and at home. Parents became more confident, empathetic, and actively involved in the character-building process. The communication forum served as a sustainable collaboration platform, fostering a synergistic educational ecosystem and becoming a replicable model for religious character development in other schools.